A participação da vítima no processo penal - Cordeiro, Euller Xavier [UNESP] (2014)
This dissertation aims to research the topic of participation of victims in the Criminal Procedure. The Penal System is visibly focused on crime and criminal, however, this idea has lost ground against new studies of victimology that emphasize the victim participation in the criminal law dogmatic and have contributed for the criminal policy aimed exclusively before reintegrating author also turns now to a greater participation of victims in the Criminal Procedure. Thus, the present work has the purpose to establish what is the range and possibilities of inclusion of the victim under the Criminal Procedure, so come up with an investigation of criminological theories, such as minimalism criminal and penal abolitionism. Considering them as a theoretical is possible to analyze victim as a result of these approaches. The investigation established allows demonstrating how the rights principles in criminal proceedings, are not forgotten favoring alleged agility and better composition of criminal litigation. In fact, the inclusion of victims in the Criminal Procedure does not only occur as a manifestation of the need for technical of process acceleration. The understanding and inclusion of victims in criminal procedure, as a perspective study, is based on two ideas; first, within the mechanisms of conflict resolution aimed at consensual models of justice; and, on the other hand, participation of victims in the criminal process that occurs because of their fundamental right to compensation for damage